Determinants of Share Price Behaviour: A Detailed Review of Empirical Studies - Mohapatra, Ananta Prasad; Acharya, Pramath Nath; Mahapatra, Rudra Prasanna (Indian Journal of Finance, 2013)
Shares provide exciting opportunities for making big money. This is the reason why they have become immensely popular with the investing public as a form of investment. However, share price behaviour is a very complicated issue. This is because shares generally represent a riskier investment than do the fixed return investments. Hence, the problem of deriving a suitable basis for the evaluation of ordinary shares has been at the forefront of investment analysis. Usually, share prices are determined by the interaction of the supply and demand subject to imperfection of the stock market. In this context, the major problem is the identification and measurement of different factors which influence supply and demand. This can be achieved only by detailed review of literature on the subject. As such, the present study seeks to examine and identify the various determinants of share prices through a detailed review of empirical studies on the subject.